A Phase‐Separated SR Protein Reprograms Host Pre‐mRNA Splicing to Enhance Disease Susceptibility - Dong Yan; Jie Huang; Fengqi Tian; Haidong Shu; Han Chen; Qian Peng; Hongwei Wu; Jianlong Zhao; Anireddy S. N. Reddy; Gang Li; Yuanchao Wang; Suomeng Dong (Advanced Science)
Abstract Alternative splicing (AS) plays a vital role in the plant–microbe interaction. Modulating host precursor‐mRNA AS is a key strategy employed by multiple pathogens to subvert plant immunity. However, the underlying mechanism by which the host splicing factor regulates plant immunity remains poorly understood. Here, a plant‐conserved serine/arginine‐rich (SR) RNA splicing factor, SR30, which negatively regulates tomato immunity against the infamous Phytophthora infestans (P. infestans) is identified. SR30 governs tomato mRNA AS at a genome‐wide level and suppresses defense‐related genes AS. During P. infestans infection, SR30 is induced to form nuclear condensates via liquid–liquid phase separation driven by intrinsically disordered regions. Importantly, the phase separation property is required for the function of SR30 in disease susceptibility and the regulation of genes AS. Knockout of SR30 via CRISPR/Cas9 improves tomato disease resistance to P. infestans, P. capsici, and P. parasitica by promoting defense genes AS. These findings uncover a novel mechanism in a phase‐separated protein that regulates plant immunity by altering the AS of defense‐related genes and provides a new paradigm for engineering protein condensate in crop‐resistant breeding.